Management of Multicultural Education in Islamic Boarding Schools: A Case Study of the Implementation of Inclusivity Values in the Diversity of Santri - Muhajir, Ahmad; Adiyono, Adiyono; Patimah, Lilis (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This study aims to analyze the management and administration of multicultural education at the Nurul Muhibbin Islamic Boarding School in dealing with the cultural diversity of santri. Using a qualitative approach with a descriptive method, this study was conducted at the Nurul Muhibbin Islamic Boarding School, East Kalimantan, in November 2024. Data were collected through semi-structured interviews with ustadz (teachers), teachers, boarding school leaders, and santri (students), as well as direct observation and documentation analysis. The results showed that the understanding of multiculturalism among ustadz and santri varied, with ustadz emphasizing the importance of tolerance and unity among santri to prevent cultural conflict. In contrast, santri demonstrated adaptability through using Indonesian as a connecting language and learning the language and dialect of their respective regions. Implementing multiculturalism in Islamic boarding schools takes place naturally through integrating religious values as a unifying element and using Arabic and Indonesian as a means of communication. Despite facing challenges such as limited facilities and differences in the character of santri (Islamic boarding school students), Islamic boarding schools can create an inclusive and harmonious environment through a daily approach based on Islamic values. The conclusion of this study confirms that Nurul Muhibbin Islamic Boarding School manages cultural diversity without a formal program specifically for multicultural education. This Islamic boarding school is a real model of how multiculturalism can be effectively applied in daily life, ultimately improving social adaptation, language skills, and attitudes of tolerance among santri.